Implementasi Program Takhassus Menghafal Al-Qur’an di Sekolah Menengah Pertama Islam Terpadu Cordova Samarinda - Riska Ayu; Wahdatun Nisa; Indriana Rahmawati (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to determine the implementation of the takhassus program for memorizing the Qur'an at the integrated Islamic junior high school (SMP IT) Cordova Samarinda. In this study, the researcher chose to use a descriptive qualitative approach. The subjects of this study were the principal, representatives of teaching teachers, homeroom teachers, chief coordinators and representatives of takhassus class students. Data collection techniques were through observation, interviews and documentation. The results show that the implementation of the Takhassus program for memorizing the Qur'an at SMP IT Cordova Samarinda has gone quite well, starting from the recruitment of students, learning, to the evaluation process. This can be seen through a well-thought-out planning process, which is then continued through an implementation in the classroom as a learning program and follow-up through evaluations in order to help make decisions in the future.